Auctions with Imperfect Commitment when the Reserve May Serve as a Signal - Byoung Heon Jun; Elmar G. Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2014)
If bidders are uncertain whether the auctioneer sticks to the announced reserve, some bidders respond by strategic non-participation, speculating that the auctioneer may revoke the reserve. However, the reserve inadvertently signals the auctioneer's type, which drives a unique separating and a multitude of pooling equilibria. If one eliminates belief systems that violate the intuitive criterion , one obtains a unique equilibrium reserve price equal to the seller's own valuation. Paradoxically, even if bidders initially believe that the auctioneer is bound by his reserve almost with certainty, commitment has no value.
Keywords: D21; D43; D44; D45; 330; auctions; signaling; imperfect commitment